REFERENCE SERVICE PARADIGM OF INFORMATION AGE - Rahmah, Linggar; Safii, Moh; Martutik, Martutik (2018)
Reference services which provide printed collections are increasingly abandoned due to technological advances. The patrons on the reference service in the college library are reduced. Massive technology facilitates information retrieval so that it replaces the function of reference collections. Characteristics of students who prefer searching online information affect the service reference paradigm in the 21st century. After pre-research found instagram account that contains content reference service and has a lot of followers are Wow Fakta and Nat Geo Indonesia.This study aims to categorize the number of post instagram Wow Fakta and Nat Geo Indonesia which is included in the reference collection. This research is a quantitative content analysis. The results show that 47% of Wow Fakta are included in reference collections with the most consecutive uploaded sequences, encyclopedias, abstracts, yearbooks, almanacs, biographies. Nat Geo Indonesia of 80% is included in reference collections with the most consecutive uploaded sequences, encyclopedias, yearbooks, biographies, almanacs, abstracts and geographic sources. From this research is obtained analysis that the library can do dissemination of reference content owned as both instagram account. Paradigm of reference service from the side of the content is not abandoned but the way of dissemination that should follow the development of the era. This is the service paradigm of the 21st century reference focuses on dissemination of information and the provision of online content.